Advances in two-dimensional organic–inorganic hybrid perovskites. Issue 4 (28th February 2020) - Zhang, Fei; Lu, Haipeng; Tong, Jinhui; Berry, Joseph J.; Beard, Matthew C.; Zhu, Kai
Abstract : Recent achievements of 2D perovskites for various optoelectronic applications along with their basic properties and future opportunities are discussed. Abstract : Two-dimensional (2D) perovskites have attracted considerable interest for their promising applications for solar cells and other optoelectronics, such as light-emitting diodes, spintronics, and photodetectors. Here, we review the recent achievements of 2D perovskites for various optoelectronic applications. First, we discuss the basic structure and optoelectronic properties of 2D perovskites, including band structure, optical properties, and charge transport. We then highlight recent achievements using 2D perovskites in solar cells and beyond solar cells, including progress on various synthesis strategies and their impact on structural and optoelectronic properties. Finally, we discuss current challenges and future opportunities to further develop 2D perovskites for various applications.